Six new species of zombie-ant fungi from Yunnan in China - Dexiang Tang; Ou Huang; Weiqiu Zou; Yuanbing Wang; Yao Wang; Quanying Dong; Tao Sun; Gang Yang; Hong Yu (IMA Fungus)
Abstract Some Ophiocordyceps species infecting ants are able to manipulate the host behavior. The hosts are manipulated in order to move to location that are advantageous for fungal spore transmission. Ophiocordyceps species that are able to manipulate the ant's behavior are called "zombie-ant fungi". They are widespread within tropical forests worldwide, with relatively few reports from subtropical monsoon evergreen broad-leaf forest. Zombie-ant fungi have been described and reported in different countries worldwide. However, there were a few reports from China. This study proposed six new species of zombie-ant fungi from China based on multi-gene (SSU, LSU, TEF, RPB1 and RPB2) phylogenetic analyses and morphological characteristics. Six novel species of Ophiocordyceps from China were identified as the Ophiocordyceps unilateralis core clade, forming a separate lineage with other species. Six novel species of Ophiocordyceps with hirsutella-like asexual morphs exclusively infecting ants were presented herein, namely, Ophiocordyceps acroasca, Ophiocordyceps bifertilis, Ophiocordyceps subtiliphialida, Ophiocordyceps basiasca, Ophiocordyceps nuozhaduensis and Ophiocordyceps contiispora. Descriptions and illustrations for six taxon were provided. Five of these species were collected from the subtropical monsoon evergreen broad-leaf forest, and one was collected from the rainforest and subtropical monsoon evergreen broad-leaf forest. This work proposes that the same host of Camponotus can be infected by multiple ant pathogenic fungi, while multiple ants of Polyrhachis can be infected by the same pathogenic fungi at the same time. This study contributes towards a better understanding of the evolutionary relationship between hosts and fungi, and provides novel insights into the morphology, distribution, parasitism, and ecology of Ophiocordyceps unilateralis sensu lato. We have provided a method for obtaining living cultures of Ophiocordyceps unilateralis complex species and their asexual morphs based on the living cultures, which is of significant value for further studies of Ophiocordyceps unilateralis complex species in the future.